Active contact tracing beyond the household in multidrug resistant tuberculosis in Vietnam: a cohort study - Thi Thanh Thuy Hoang; Viet Nhung Nguyen; Ngoc Sy Dinh; Guy Thwaites; Thu Anh Nguyen; H. Rogier van Doorn; Frank Cobelens; Heiman F. L. Wertheim (BMC, 2019)
Abstract Background Currently in Vietnam contact tracing for multidrug-resistant tuberculosis (MDR-TB) entails passive case finding among symptomatic household contacts who present themselves for diagnosis. Close contacts of MDR-TB cases are therefore not identified adequately. We assessed the added value of active contact tracing within and beyond households using social network questionnaires to identify close contacts of MDR-TB patients in Vietnam. Methods We conducted a cohort study using social network questionnaires in which contacts were identified by MDR-TB patients, including contacts from 'high risk' places like work. Contacts of MDR-TB patients were followed up and screened over a period of at least 6 months. This included two active screenings and any unscheduled passive screening of self-referred contacts during the study period. Results Four hundred seventeen contacts of 99 index cases were recruited, 325 (77.9%) and 160/417 (38.4%) contacts participated in the first and second screenings, respectively. The first screening detected one TB case but the bacteria were not MDR. From passive screening, a household contact was diagnosed with TB meningitis but not through our active approach. Social network analysis showed that only 1/17 (5.9%) high-risk places agreed to cooperate and were included in the screening, and no MDR-TB cases were detected. There were two pairs of index cases (identified separately) who were found to be contacts of each other and who had been diagnosed before the study started. Conclusions No new MDR-TB cases were detected using social network analysis of nearly 100 MDR-TB index cases, likely due to a relatively short follow up time, and loss to follow up (lack of cooperation from contacts or high risk places and lack of available resources in the National Tuberculosis Control Programme).